2021
DOI: 10.5194/essd-2021-16
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Harmonization of global surface ocean pCO<sub>2</sub> mapped products and their flux calculations; an improved estimate of the ocean carbon sink

Abstract: Abstract. Air-sea flux of carbon dioxide (CO2) is a critical component of the global carbon cycle and the climate system with the ocean removing about a quarter of the CO2 emitted into the atmosphere by human activities over the last decade. A common approach to estimate this net flux of CO2 across the air-sea interface is the use of surface ocean CO2 observations and the computation of the flux through a bulk parameterization approach. Yet, the details for how this is done in order to arrive at a global ocean… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…For a better assessment of the reconstruction uncertainty, future studies should include realistic uncertainties of these data, and also of local (sub-)skin effects of temperature and salinity as suggested in Watson et al (2020). Additional sources of uncertainty in the computation of air-sea fluxes are discussed by Wanninkhof (2014); Woolf et al (2019); Fay et al (2021). These studies have demonstrated the strong impact of different wind field products and model parameterizations on the gas transfer velocity k in Eq.…”
Section: Model Errors and Uncertaintiesmentioning
confidence: 99%
“…For a better assessment of the reconstruction uncertainty, future studies should include realistic uncertainties of these data, and also of local (sub-)skin effects of temperature and salinity as suggested in Watson et al (2020). Additional sources of uncertainty in the computation of air-sea fluxes are discussed by Wanninkhof (2014); Woolf et al (2019); Fay et al (2021). These studies have demonstrated the strong impact of different wind field products and model parameterizations on the gas transfer velocity k in Eq.…”
Section: Model Errors and Uncertaintiesmentioning
confidence: 99%
“…This variability is a result of ocean mixing, equilibration kinetics between the atmosphere and ocean, biological processes, and thermal effects on pCO2(sw). Filling temporal and spatial data gaps in the observational coverage of pCO2(sw) can therefore be challenging (Hauck et al, 2020;Fay et al, 2021) and a variety of strategies have been attempted over several decades (Takahashi et al, 1993;Rödenbeck et al, 2015), becoming even more prevalent and varied in the literature over time.…”
mentioning
confidence: 99%
“…Briefly, statistical interpolations (Takahashi et al, 1993;Rödenbeck et al, 2014;Jones et al, 2015;Shutler et al, 2016), multiple linear regressions (Schuster et al, 2013;Iida et al, 2015;Becker et al, 2021), machine-learning-based regression methods (Landschützer et al, 2013;2014;2016;Nakaoka et al, 2013;Zeng et al, 2014;Laruelle et al, 2017;Ritter et al, 2017;Gregor et al, 2017;Chen et al, 2019;Denvil-Sommer et al, 2019), and biogeochemical-model-based approaches (Valsala and Maksyutov, 2010;Majkut et al, 2014;Verdy and Mazloff, 2017) have been common tactics, each one with its own strengths and weaknesses. Recently, ensemble averages of multiple data-or model-based approaches have become a popular option as well (Gregor et al, 2019;Lebehot et al, 2019;Fay et al, 2021).…”
mentioning
confidence: 99%
See 2 more Smart Citations